Acute hypersensitivity pneumonitis associated with mushroom worker’s lung – a case report - Makuch, Marcelina; Milanowski, Janusz; Palonka, Michał; Makuch, Marcin; Michnar, Marek (Journal of Education, Health and Sport, 2019)
Hypersensitivity pneumonitis (HP), also known as extrinsic allergic alveolitis is a non-IgE mediated allergic reaction to inhalation of an allergen. There are more than 200 allergens known to cause this condition, but the list of antigens responsible for the development of HP is constantly expanded. Dangerous agents are usually inhaled at the workplace, so we may distinguish the following patients at risk of HP: farmers, pigeon breeders, mushroom workers, cheese employees or even malt workers. Mushroom worker’s lung (MWL) has been described in workers exposed to mushroom spores or to inhaled antigens from compost (mostly thermophilic actinomycetes).